Total elbow arthroplasty for end-stage rheumatoid elbow arthritis with major instability: a case report - Sousa, Diogo A.; Sapage, Rita; Branco, Carlos; Sousa, Rita; Reis, Joao; Lopes, Antonio L.; Cruz, Antonio G. (International Journal of Research in Orthopaedics, 2020)
A 73 years old female diagnosed with rheumatoid arthritis for over 30 years with an end-stage right elbow arthritis (stage V of Larsen’s classification) with a major instability. The patient presented gross deformity and severe pain with critical limitation of limb function. The patient was treated with a total elbow arthroplasty with an intraoperative olecranon fracture. At six months follow up, the patient presents with an excellent active range of motion and painless joint, without daily activities limitation.